PENGELOLAAN SUMBERDAYA PERIKANAN BERKELANJUTAN DI KABUPATEN TIMOR TENGAH UTARA BERBASIS PENDEKATAN BIOEKONOMI - Maria Yanti Akoit; Mardit Nalle (Jurnal Agribisnis Indonesia, 2018)
In a study of sustainable management of fishery resources in the waters of the North Insana the District of  Wini aims to determine the optimal effort (E*), the optimum yield (Y*) and sustainable economic benefits (π*) using descriptive methods and techniques of analysis with quantitative analysis through bioeconomic approach  of Gordon-Schaefer with CYP technique (Clark, Yoshimoto and Pooley). Through bioeconomic approach it is known that the exploitation status of small pelagic fisheries. Time series data used are the result of catching the small pelagic fish paying fishing gear, gill nets, trolleys and fishing rods. The results showed that the rate of utilization of small pelagic fish resources at the District of North Insana Wini waters conditions biological in the underfishing and economic conditions in the condition underexploited.